Association between renal function trajectories and risk of cardiovascular disease: a prospective cohort study - Xuehong Xu; Rulin Ma; Xianghui Zhang; Heng Guo; Mulatibieke Keerman; Xinping Wang; Yu Li; Remina Maimaitijiang; Jia He; Shuxia Guo (Annals of Medicine)
Introduction It is unclear whether changing trajectories of renal function will increase the risk prediction information of cardiovascular disease (CVD). This study aimed to evaluate the trajectory patterns of estimated glomerular filtration rate (eGFR) and the association between eGFR trajectories and CVD risk.Methods A total of 4742 participants were included in the cohort from the 51st Regiment of Xinjiang Production and Construction Corps. The study endpoint was the occurrence of CVD events. eGFR trajectories were identified using a linear mixed-effects model in four distinct patterns. Multivariate Cox proportional hazards models analysed the correlations between eGFR trajectories and CVD.Results During a median follow-up period of 5.7 years, a total of 559 (11.8%) CVD, 404 (8.5%) myocardial infarction (MI), 244 (5.2%) ischemic stroke (IS), and 62 (1.3%) heart failure (HF) incidents occurred. After multivariable adjustment, gradual decline trajectory increased the risk of CVD (HR 1.42, 95% CI 1.16–1.74), MI (HR 1.41, 95% CI 1.11–1.79), and IS (HR 1.41, 95% CI 1.04–1.92); gradual increase trajectory reduced the risk of CVD (HR 0.40, 95% CI 0.25–0.64) and MI (HR 0.49, 95% CI 0.29–0.81). Consistent results were obtained in sensitivity and subgroup analyses.Conclusions Decline and increase of renal function were related to the risk of CVD, MI, and IS in the rural areas of Xinjiang. Monitoring eGFR changing trajectory is of great significance in improving the risk of CVD.